2020
DOI: 10.1080/09297049.2020.1750577
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of children and adolescents’ mood and self-concept after acquired brain injury

Abstract: Few studies have examined the self-reported mental health of children with an acquired brain injury (ABI). The current study aimed to: 1) identify levels of child-reported depressive and anxiety symptoms and poor self-concept, 2) investigate demographic and injury-related factors associated with children's mood and self-concept, and 3) examine associations between children's self-reported mental health and parents' reports of children's emotional and behavioral functioning in children specifically with traumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…There were no differences in the rate of change over time for girls and boys. This finding is consistent with prior literature suggesting vulnerability of girls after both TBI ( 10 , 69 72 ) and the broader category of pediatric acquired brain injury ( 73 ). Similarly, increased internalizing and ADHD symptoms were noted in girls compared to boys when assessed during the first year after injury after accounting for pre-injury ratings ( 5 ).…”
Section: Discussionsupporting
confidence: 92%
“…There were no differences in the rate of change over time for girls and boys. This finding is consistent with prior literature suggesting vulnerability of girls after both TBI ( 10 , 69 72 ) and the broader category of pediatric acquired brain injury ( 73 ). Similarly, increased internalizing and ADHD symptoms were noted in girls compared to boys when assessed during the first year after injury after accounting for pre-injury ratings ( 5 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, lower personal expectations may be the result of changes in self-image and mattering that was described in the current study. These findings support previous research that has found that self-image is impacted in adults (Caplan et al, 2016), adolescents (Snyder, 2019), and children (Hendry et al, 2020;Iadevaia et al, 2015;Todd et al, 2018) post-concussion. Similar to the impact on mattering observed in the current study, Valovich McLeod et al (2017) found that athletes demonstrated significant concern for letting their team and family down, and not being able to fulfill their role as an athlete.…”
Section: Schoolsupporting
confidence: 91%
“…Second, patients with ABI are often diagnosed in comorbidity with depression or emotional disorders ( Hendry et al, 2020 ). In the current experience, parents reported that the relationship with the therapist contributed to supporting the child in facing an extremely critical period, with positive effects on mood and energy level.…”
Section: Discussionmentioning
confidence: 99%